PREVALENCE OF OLDER DRIVERS IN BRAZIL: RESULTS FROM VIGITEL 2018 - Eduardo Hauser; Aline Rodrigues Barbosa; Andréa Holz Pfützenreuter (Brazilian Society of Geriatrics and Gerontology, 2021)
OBJECTIVE: To estimate the prevalence of Brazilian older adults who drive a car/ride a motorcycle, according to sociodemographic characteristics. METHODS: This cross-sectional study uses data from the 2018 Surveillance System for Risk and Protective Factors for Chronic Diseases by Telephone Survey (Vigitel). The prevalence of drivers was determined by an affirmative answer to the following question: "Do you drive a car, motorcycle and/or other vehicle?". RESULTS: Among the 15 333 individuals aged 65 and over living in Brazilian capitals and the Federal District, the overall prevalence of drivers was 28.73% (95%CI 27.22 - 30.29) and was higher among men (53.37%; 95%CI 50.45 - 56.28), those with higher education (65.44%; 95%CI 61.98 - 68.75), and individuals aged 65 to 69 years (35.7%; 95%CI 33.06 - 38.61). Among the regions of Brazil, prevalence varied from 35% (Midwest and South) to approximately 22% (North and Northeast). Florianopolis (42.2%; 95%CI 38.05 - 46.47) and Palmas (40.32%; 95%CI 32.74 - 48.38) were the cities with the highest prevalence of older drivers. CONCLUSIONS: Characteristics such as sex, age group, region, and state capital of residence affect the prevalence of older drivers. Our results contribute to knowledge about how older adults choose to move around in large Brazilian cities, enabling proposal of strategies to improve the quality of this population's displacement.